2014
DOI: 10.1016/j.ijid.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of NS3 and NS5A non-structural genes of hepatitis C virus genotype 3a local isolates in apoptosis

Abstract: It is concluded that both of the non-structural genes, NS3 and NS5A, of HCV play important roles in the hepatocarcinogenesis of HCV by interacting directly or indirectly in different manners with the p53 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Moreover, HCV proteins (NS5A, NS3, core protein) can interact with p53 (6,18,31,39). Lan et al (18) showed that NS5A protein suppress p53-mediated transcriptional transactivation and apoptosis during HCV infection, which may contribute to hepatocarcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, HCV proteins (NS5A, NS3, core protein) can interact with p53 (6,18,31,39). Lan et al (18) showed that NS5A protein suppress p53-mediated transcriptional transactivation and apoptosis during HCV infection, which may contribute to hepatocarcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Lan et al (18) showed that NS5A protein suppress p53-mediated transcriptional transactivation and apoptosis during HCV infection, which may contribute to hepatocarcinogenesis. Sabri et al (39) analyzed the interaction of NS3 and NS5A proteins with p53, and they concluded that these HCV proteins play important roles in hepatocarcinogenesis by downregulating expression of the p53 gene. Deng et al (6) found that NS3 protein plays an important role in hepatocarcinogenesis and inhibits p53 function in an NS3 sequence-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the combination between NS3 and p53 upregulates UBD expression and UBD is involved with tumorigenesis and malignancy [ 25 , 26 , 31 , 42 ], we wonder whether interfering UBD with RNAi can reverse NS3-mediated development of HCC. To confirm this, we disrupted the expression of UBD with UBD-specific siRNAs in HepG2 cells (shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, overexpressed UBD facilitated HCC proliferation through degrading Wnt-induced secreted protein-1 [ 52 ]. At the same way, NS3, a serine protease, which is responsible for the cleavage of at least four sites (NS3/4A, NS4A/4B, NS4B/5A, and NS5A/5B junctions), has been reported to contribute the development of HCC through inhibiting p53-mediated apoptosis [ 42 ]. In this study, UBD was significantly upregulated by NS3 in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%